Landslide frequency and its relationship with urban development in landform above groundwater basin area of Bogor, Indonesia - Yulia Amirul Fata; Hendrayanto Hendrayanto; Nur Febrianti (Brawijaya University, 2022)
The presence of groundwater in the groundwater basin increases the potential of rainwater seeping into the soil and reaching the groundwater system. As a result, the soil takes longer to get saturation and maintain its stability. The groundwater basin stability is also influenced by the layer's lithological, soil, and morphological properties above the groundwater system and human activities on the land. The purpose of this study was to characterize the groundwater basins, non-groundwater basins, and landslides that happened in those locations in the tropical region of Bogor, Indonesia. The characteristics of landslide events, including lithological, groundwater table, soil, slope, and land use in each groundwater basin zone, were evaluated using quantitative descriptive analysis. The result showed 686 landslides from 2015 to 2019 that mainly occurred in the discharge zone, characterized by slope classes of >45%, soil types of Technosol (Inceptisols), Quaternary lithology periods, and settlement land use. The landslide type in the groundwater basin is dominated by surface landslides, while the landslides in the non-groundwater basin are mostly shallow landslide types.